The impact of vocational training on labor market outcomes in the Philippines. - Vandenberg, Paul; Laranjo,Jade (Metro Manila, Philippines Asian Development Bank, 2020)
The paper analyzes how post-secondary technical and vocational education and training (TVET) impacts labor market outcomes in the Philippines. Findings from the study show that TVET graduates in the Philippines earn significantly higher wages than those who entered the job market with a secondary school education or below. However, individuals who both trained in TVET and pursued tertiary education earn less than those with secondary school or below. This counterintuitive result is explained by the tendency for such dual-level individuals to complete the lowest level of TVET.
Keywords: Vocational education -- Economic aspectst -- Philippines; Vocation education -- Philippines; Electronic books